2022
DOI: 10.3389/fphar.2022.835136
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics and Precision Medicine Approaches for the Improvement of COVID-19 Therapies

Abstract: Many drugs are being administered to tackle coronavirus disease 2019 (COVID-19) pandemic situations without establishing clinical effectiveness or tailoring safety. A repurposing strategy might be more effective and successful if pharmacogenetic interventions are being considered in future clinical studies/trials. Although it is very unlikely that there are almost no pharmacogenetic data for COVID-19 drugs, however, from inferring the pharmacokinetic (PK)/pharmacodynamic(PD) properties and some pharmacogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 338 publications
(334 reference statements)
0
17
0
1
Order By: Relevance
“…These genes are highly polymorphic (e.g. CYP3A4/5 , CYP2B6 , CYP2C8 , CYP2C9 , CYP2C19 , CYP2D6 ) and are characterized by a wide geographic variability ( Zhou et al, 2017 ; Biswas et al, 2020 ; Sukprasong et al, 2021 ) interacting with large part of those drugs specifically used in COVID-19 ( Sukasem et al, 2013 ; Biswas et al, 2022 ). Interestingly, many clinical complications of COVID-19 belong to the same group of comorbidities responsible for the poor prognosis, and drugs acting as anti-inflammatory, antithrombotic (anti-coagulant and anti-aggregant), anti-hypertensive or with lipid-lowering action, have marked pharmacogenomics features resembling those belonging to the lipoproteins and homocysteine homeostasis genes ( Parmeggiani et al, 2008 ; Gemmati et al, 2009 ; Gemmati et al, 2016 ; Tisato et al, 2019 ; Cappadona et al, 2021 ; Tisato et al, 2021 ; Biswas et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…These genes are highly polymorphic (e.g. CYP3A4/5 , CYP2B6 , CYP2C8 , CYP2C9 , CYP2C19 , CYP2D6 ) and are characterized by a wide geographic variability ( Zhou et al, 2017 ; Biswas et al, 2020 ; Sukprasong et al, 2021 ) interacting with large part of those drugs specifically used in COVID-19 ( Sukasem et al, 2013 ; Biswas et al, 2022 ). Interestingly, many clinical complications of COVID-19 belong to the same group of comorbidities responsible for the poor prognosis, and drugs acting as anti-inflammatory, antithrombotic (anti-coagulant and anti-aggregant), anti-hypertensive or with lipid-lowering action, have marked pharmacogenomics features resembling those belonging to the lipoproteins and homocysteine homeostasis genes ( Parmeggiani et al, 2008 ; Gemmati et al, 2009 ; Gemmati et al, 2016 ; Tisato et al, 2019 ; Cappadona et al, 2021 ; Tisato et al, 2021 ; Biswas et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…43 CRHR1, gene of receptor binding, is associated with the efficacy of corticosteroids. 44 Consistently, an open-label randomized controlled trial showed that taking dexamethasone, a corticosteroid, may lower the risk of 28-day mortality by 17% COVID-19-hospitalized patients. 45 Our bi-directional Mendelian randomization study adds to the limited evidence on the causal relationship between RA and COVID-19.…”
Section: Discussionmentioning
confidence: 94%
“…One initiative that potentially could facilitate and promote the use of precision medicine towards tackling COVID-19 is the creation of the open-access database named the COVID-19 Genomics and Precision Health database (COVID-19 GPH) by the Genomics and Precision Public Health at the CDC, providing important information such as pathogenic information and the contribution of genomics ( Yu et al, 2022 ). To date, current COVID-19 therapeutics have never undergone multifactorial drug-gene interactions; within this framework, it has been suggested that these therapeutics should undergo evaluation for their genetic associations of relevant metabolic or transporter genes, which would allow for the evaluation of their safety and effectiveness and also promoting precision COVID-19 therapeutics ( Biswas et al, 2022 ). Another strategy that has been investigated in personalized medicine for COVID-19 patients is the use of autologous peripheral blood stem cells and plasma ( Balzanelli et al, 2022 ).…”
Section: High-content Tissue Models Toward Personalized Medicine For ...mentioning
confidence: 99%